Pengaruh PDRB, Tingkat Pendidikan dan Upah Minimum Terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan Tahun 2016 – 2020 - Aqyun, Qurata; Siregar, Syahrituah (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine the relationship between GRDP, Education Level, and Minimum Wage on Workforce Absorption in South Kalimantan Province in 2016-2020 and choose the most dominant factor influencing employment in regencies/cities in South Kalimantan Province. During the 2016-2020 period. This type of research is descriptive quantitative. The data collection technique that has been obtained uses a panel data regression analysis tool, and the fixed effect application model Eviews 10 is selected. These results show that GRDP, Education Level, and Minimum Wage affected Labor Absorption in South Kalimantan Province in 2016-202. Minimum Wage Variables are The most dominant variable influencing labor absorption in South Kalimantan Province in 2016-2020.